Heterostructured mixed metal oxide electrocatalyst for the hydrogen evolution reaction - Pratama, Dwi Sakti Aldianto; Haryanto, Andi; Lee, Chan Woo (Frontiers in Chemistry, 2023)
The hydrogen evolution reaction (HER) has attracted considerable attention lately because of the high energy density and environmental friendliness of hydrogen energy. However, the lack of efficient electrocatalysts and high price hinders its wide application. Mixed metal oxide (MMO) electrocatalyst emerges as a potential HER catalyst, especially providing heterostructured interfaces that can efficiently overcome the activation barrier for hydrogen evolution reaction, compared to a single-phase metal oxide catalyst. In this mini-review, several design strategies for the synergistic effect of the MMO catalyst on HER are summarized. In particular, metal oxide/metal oxide and metal/metal oxide interfaces are explained with fundamental mechanistic insights. Finally, existing challenges and future perspectives for HER are discussed.